A clinical description of meniscal pathology with different genesis - Baburkina, Elena; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The authors examined pathology of the knee joint menisci depending upon its genesis. Statistically analysed were the parameters, which characterized the patients: sex, age, pathological combinations, clinical signs of some knee joint pathology, namely a degree of limitations of the knee joint movements, presence of axial deformities (varus, valgus), sagittal loss of axiation, a larger lateral mobility on the knee joint level and an increased patella mobility, an angle of the patellar ligament Q. The analysis of clinical observations of patients with different genesis of their meniscus pathology revealed that prevailing were cases with meniscogenic syndrome, caused by hereditary predisposition, mostly indirect (with dysplasia of the femoropatellar joint and frontal deformities). In the group of patients with traumatic and pathic pathology of menisci the diagnosis included only one nosological unit: impairment of a meniscus. Meniscogenic syndrome, caused by hereditary predisposition (direct and indirect), was accompanied by other dysplastic syndromes (SFJD, SPI, VDS, VDS).